Ecotoxicological Characterization of Type C Killer Whales From Terra Nova Bay (Ross Sea, Antarctica): Molecular Biomarkers, Legacy, and Emerging Persistent Organic Contaminants - Panti, Cristina; Muñoz-Arnanz, Juan; Marsili, Letizia; Panigada, Simone; Baini, Matteo; Jiménez, Begoña; Fossi, Maria Cristina; Lauriano, Giancarlo (Frontiers in Marine Science, 2022)
Among killer whale forms, the type C is a fish-eating form and is the most common in the Ross Sea. In the austral summer 2015, a study was conducted to evaluate the toxicological hazard these marine mammals face in the Antarctic ecosystem. Seven biopsy samples were collected from adult individuals (5 males and 2 females) in the surroundings of the Italian Research Station Mario Zucchelli, in Terra Nova Bay, by remote dart sampling from the pack ice. The accumulation levels of persistent organic pollutants (POPs) such as legacy (DDTs, PCBs, HCB) and emerging (PBDEs and DP) were measured. Moreover, the protein expression of cytochrome P450 (CYP1A1 and 2B) and the mRNA level variations of the peroxisome proliferator-activated receptors α and γ (PPARα-γ) and the Estrogen Receptor α (ERα), Aryl Hydrocarbon receptor (AhR) and Cyp1a were evaluated. Twenty PCB congeners, six DDTs, HCB, three HCHs, and fourteen brominated BDEs and DP-syn and anti-isomers were analysed on freeze-dried blubber biopsy samples by GC-MS. The protein expression was evaluated by Western Blot and the mRNA levels were quantified by quantitative Real-Time PCR. The average abundance pattern for the contaminants was DDTs>PCBs>HCB>HCHs≈PBDEs>>DP. Contaminant levels resulted to be lower when compared to existing data from Antarctic type C killer whales from the McMurdo Sound (Ross Sea) and those reported for fish-eating killer whales worldwide. The mRNA levels of the five target genes were successfully quantified, but no statistical correlation was found with POP levels, suggesting that either the low levels of quantified POPs in blubber may not significantly affect the biological responses investigated, or that other stressors could contribute to the alterations of the molecular biomarkers. Although the results showed a lower risk related to contamination compared to more impacted areas, this study provides baseline data for the conservation of this species in an area with high ecological value, recently declared as the largest Marine Protected Area in Antarctica, where pollutants should remain at minimum levels despite increasing multiple stress existing in the region.